2009
DOI: 10.1111/j.1365-2524.2008.00796.x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed transfer from hospital to community settings: the older person's perspective

Abstract: Prevention and management of delayed transfer of older people from hospital to community settings is an enduring issue in industrialised societies and is the subject of many recent policies in the United Kingdom. A deeper, evidence-based understanding of the complex organizational and interprofessional issues which contribute to delays in transfer has emerged in recent years. Despite this, and the relative success of recent policies, two recent reviews of the area highlight the lack of studies on patients' per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
112
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(115 citation statements)
references
References 28 publications
(30 reference statements)
0
112
0
Order By: Relevance
“…Lack of information concerning the discharge process was apparent in several of the studies exploring the patients' perspective on discharge planning (Benten and Spalding 2008;Ellis-Hill et al 2009;Foss and Hofoss 2011;McKain et al 2005;Perry et al 2011;Swinkels and Mitchell 2008). Information was provided orally.…”
Section: Informationmentioning
confidence: 99%
See 3 more Smart Citations
“…Lack of information concerning the discharge process was apparent in several of the studies exploring the patients' perspective on discharge planning (Benten and Spalding 2008;Ellis-Hill et al 2009;Foss and Hofoss 2011;McKain et al 2005;Perry et al 2011;Swinkels and Mitchell 2008). Information was provided orally.…”
Section: Informationmentioning
confidence: 99%
“…Information was provided orally. In one study by Benten and Spalding (2008) (Perry et al 2011;Swinkels and Mitchell 2008) documented that some patients were not aware of their own formal discharge plan. One study (Foss and Hofoss 2011) revealed sparsely information to patients about discharge.…”
Section: Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…Aside from the additional costs of delayed hospital discharge, qualitative interviews indicate that uncertainty in having their hospital discharge delayed and guilt about being identified as a 'bed blocker' can cause considerable anxiety and stress to patients at the end of life. 53,54 When provision for support outside hospital is in place, arranging timely and appropriate transport can cause further delays. 55 …”
Section: Delayed Dischargesmentioning
confidence: 99%